Periodontal disease in individuals with a genetic risk of developing arthritis and early rheumatoid arthritis: A cross-sectional study (2016)
Recent consensus emphasizes the importance of studying individuals at risk for rheumatoid arthritis (pre‐RA) and those with early RA (eRA). Periodontal tissues have been recently evaluated, but these studies are limited. To evaluate the periodontal condition, immunoglobulin (Ig)G subclasses against Porphyromonas gingivalis in individuals with pre‐RA and eRA were compared with controls to establish an association between periodontal infection markers and rheumatic activity. Rheumatologic and periodontal condition was evaluated in 119 individuals with pre‐RA, 48 patients with eRA, and matched controls. P. gingivalis IgG1 and IgG2 were analyzed. C‐reactive protein, erythrocyte sedimentation rate (ESR), rheumatoid factor, anticitrullinated protein antibodies (ACPAs), and RA activity were measured. The groups were compared with McNemar test and paired t‐test. Conditional logistic regression was performed for pre‐RA confounders, and χ2 test was used to evaluate periodontal variables and RA activity indices. Pre‐RA individuals showed significantly higher levels of plaque index (P = 0.01) and bleeding on probing (P = 0.03) and higher severity of periodontal disease (P = 0.02). Periodontitis was associated with pre‐RA (odds ratio, 3.39; 95% confidence interval, 1.64 to 7.01) but not with eRA. In pre‐RA, P. gingivalis–specific IgG2 was associated with ACPAs (P = 0.049) and disease severity visual analog scale (P = 0.03). In eRA, IgG2 against P. gingivalis was associated with ESR (P = 0.046) and ACPAs (P = 0.04). P. gingivalis was associated with ACPAs (P = 0.04). This study shows that individuals with pre‐RA have significant inflammatory periodontal involvement. There was a significant association between IgG against P. gingivalis and ACPAs in pre‐RA and markers of RA activity in individuals with eRA.